Pengenalan Sains Bagi Anak Usia Dini Menggunakan Metode Permainan - Anggraeni Mashinta Sulistyani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: Early age is fundamental phase for individual development that called golden age. Experience faced by children will shape the experience that carried for a lifetime. Implentation in early childhood requires appropriate steps. Therefore, introduction of science must have basic properties: simple, character recognition, concrete, contextual,balanced between physical and mental activities, be careful with the question of why, according to the child’s development, according to the needs of individuals, developing intelligence, suitable with children’s learning style, and integrated. Learning also presented using the game to suit the age level of the child, creative, interesting, and fun. The learning resources that can be used, among others, that are near child like at home or school, limbs, also related directly correspond to needs of early childhood. Thus, the introduction of science for young children using these games can improve cognitive abilities such as problem-solving abilities. Children are also more enthusiastic, active, and happy. Keywords: introduction to science, early childhood, game method.